PKT Hypermarket / Mohd Afifuddin Zaharuddin - Zaharuddin, Mohd Afifuddin (2022)
PKT Hypermarket name from Pengkalan Kubur Trading and start operation on 27 September 2007, PKT hypermarket provide home grocery also have a few branches in Kelantan and Terengganu. PKT hypermarket attract customers who have family in line with the tagline' Pusat Membeli Belah Sekeluarga'. For this project i would say this is about to be a major rebrand for PKT hypermarket because i applied a new and simple design and stay with blue and yellow color to not change their iconic and strong identity. Besides that i applied their emotional selling proposition (ESP) this company in their new logo for attract more customers.